Diagnostics of anodic stripping mechanisms under square-wave voltammetry conditions using bismuth film substrates - Mirceski, Valentin; Hocevar, Samo B; Ogorevc, Bozidar; Gulaboski, Rubin; Drangov, Ivan (American Chemical Society (ACS), 2012)
A mechanistic study to provide diagnostics of anodic stripping electrode processes at bismuth-film electrodes is presented from both theoretical and experimental points of view. Theoretical models for three types of electrode mechanisms are developed under conditions of square-wave voltammetry, combining rigorous modeling based on integral equations and the step function method, resulting in derivation of a single numerical recurrent formula to predict the outcome of the voltammetric experiment. In the course of the deposition step, it has been assumed that a uniform film of the metal analyte is formed on the bismuth substrate, in situ deposited onto a glassy carbon electrode surface, without considering mass transfer within either the bismuth or the metal analyte film. Theoretical data are analyzed in terms of dimensionless critical parameters related with electrode kinetics, mass transfer, adsorption equilibria, and possible lateral interactions within the deposited metal particles. Theoretical analysis enables definition of simple criteria for differentiation and characterization of electrode processes. Comparing theoretical and experimental data, anodic stripping processes of zinc(II), cadmium(II), and lead(II) are successfully characterized, revealing significant differences in their reaction pathways. The proposed easy-to-perform diagnostic route is considered to be of a general use while the bismuth film exploited in this study served as a convenient nonmercury model substrate surface.